Blood pressure self-monitoring practice and associated factors among adult hypertensive patients on follow-up at South Wollo Zone Public Hospitals, Northeast Ethiopia. Issue 1 (23rd March 2023) - Edmealem, Afework; Geleta, Esmael; Mengesha, Zemen; Tegegne, Belachew; Ademe, Sewunet; Liknaw, Tiliksew
Abstract : Background: Hypertension is a silent killer that causes serious health issues in all parts of the world. It is risk factor for cardiovascular disease, stroke and kidney disease. Self-monitoring practice has been identified as an important component of hypertension management. Hence, this study aimed to assess blood pressure (BP) self-monitoring practice and associated factors among adult hypertensive patients on follow-up in South Wollo Zone public hospitals, Northeast Ethiopia. Methods: Hospital-based cross-sectional study was conducted from 1 June 2022 to 30 June 2022, among 336 adult hypertensive patients on follow-up at selected South Wollo Zone public hospitals. Data were collected by using self-administered pretested structured questionnaires; the collected data were entered into Epi-data V.4.6 and then exported to SPSS V.25 software for analysis. Descriptive statistics such as frequency and percentage were used to describe the study participants. Tables and texts were used for data presentation. Binary logistic regression was conducted to test the association between the independent and dependent variables. Adjusted OR (AOR) with 95% CI was estimated to identify the factors associated with BP self-monitoring and the level of significance was declared at p<0.05. Results: The proportion (95% CI) of BP self-monitoring practice among hypertensive patients in South Wollo Zone Public Hospitals was 8.93% (95% CI 6.3% to 12.5%). In the multivariable analysis, urban residence (AOR 3.97, 95% CI (1.11 to 14.20)), comorbidity (AOR 4.80, 95% CI (1.23 to 18.69)), regular healthcare professional visit (AOR 4.64, 95% CI (1.02 to 21.14)), advice on the type of devices used for BP self-monitoring (AOR 5.26, 95% CI (1.49 to 18.58)) and knowledge on hypertension self-care (AOR 13.13, 95% CI (4.21 to 40.99)) were positively associated with BP self-monitoring practice. Conclusion: The proportion of BP self-monitoring practice was low. Living in urban areas, comorbidity, regular healthcare professional visits, advice on the type of devices used for BP self-monitoring, and knowledge of hypertension self-care were positively associated with BP self-monitoring practice.